The value of islamic education in the yaa qowiyyu tradition in Jatinom - Elisa Putri Kholifah; Muh. Wasith Achadi; Himad Ali (At Turots: Jurnal Pendidikan Islam, 2024)
The yaa qowiyyu tradition is one of the traditions that is still being preserved for generations in Jatinom village, Jatinom district, Klaten regency. This tradition is a form of respect for kyai ageng gribig as a scholar figure who plays a role in spreading Islamic teachings in Jatinom District. In fact, many things have changed following the development of zama but do not disturb the preservation of the originality of this tradition remains as it should be, only adding a few cultural festivals to be more relevant to the development of the times and more easily accepted by young imaginary. This study aims to find out the value of education and religiosity contained in the Yaa Qowiyyu Tradition in Jatinom Village, Jatinom District, Klaten Regency. This research is included in qualitative research with an ethnographic approach. The data collection technique in this study uses observation, interviews and documentation. The three methods are expected to be able to complement each other so as to obtain the expected information. Furthermore, in the data analysis process, the researcher uses a method consisting of three steps, namely data condensation, data presentation, and conclusion drawn. The results of the study show that the Yaa Qowiyyu tradition is full of educational values and religiosity values. The main icon in this tradition is the spread of apem on Friday after Friday prayers, which then the sense of tolerance of each community who follows the implementation is also included in one of the educational values applied. Then, the value of religiosity is such as a form of gratitude for the blessings given by Allah SWT by issuing alms through the making of apem to be distributed to everyone who participates in the implementation of the tradition.